ON THE EXTENDABILITY OF GRIESMER ARCS (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2013)
We prove a new sufficient condition for the extendability of Griesmer arcs with certain parameters.